Continuidade e Transformação. Projecto de reabilitação do edifício do antigo Orfeão de Viseu - Mélissa Fernandes Almeida (2018)
The concern for the preservation of building heritage is a secular issue. From an early age, Man looked to safeguard testimonies of the past that served him as a memory of an obsolete time. At a time when there is growing commercialization of culture in urban centers, there has been a tendency to transform existing buildings in historic centers into objects devoid of their identity. Fachadism as well as the inclusion of programs that collide with the own identity of the site are only two of the several attacks that have plagued the present historical centers. The present dissertation tries to oppose this tendency with the project of rehabilitation of "edifício do antigo Orfeão de Viseu" and its reconversion in a dance school. The building, dating from the end of the 19th century, is located in the historic center of Viseu, with clear signs of abandonment. The dance school emerged as an inclusive program that fit the structure of the old building while at the same time would contribute to the local dynamism. The investigation focused on five topics: Theoretical context; Site; Building; Program; Proposition. After introducing the problem raised initially and in an incessant search to maintain the identity of the building, the idea of rehabilitation embraced specially the three intermediate topics, considering them as constraints of any intervention in the Heritage. In addition to an exhaustive study, the visits and survey drawings proved to be indispensable work tools for the realization of this project. As it is essentially a practical exercise, the proposition has also been derived from personal convictions and influences, which are naturally included in the process. This exam was intended not only to present the evolutionary process of the designed proposition but also to approach the condition of the site and the choice of the program as valuable purposes in the rehabilitation project, as well as a thorough knowledge about the building to be preserved.